2018
DOI: 10.1111/jcpp.12955
|View full text |Cite
|
Sign up to set email alerts
|

The impact of school support on depression among adolescent orphans: a cluster‐randomized trial in Kenya

Abstract: School support for orphans may help to buffer against the onset or worsening of depression symptoms over time, promoting resilience among an important at-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Likewise, Simmons-Zuilkowski [ 105 ] found that in South Africa enrollment rates among the very poor are lower because of cost of uniforms. In Kenya, Mutengi [ 106 ] found a statistically significant link between uniform cost and education access, and Green et al [ 107 ], Sitieni and Pillay [ 108 ] and Cho et al [ 109 ] describe free uniform as part of support and incentive packages for at-risk children to attend school [ 110 ]. In Ghana, Alagbela [ 111 ] and Akaguri [ 112 ] show that uniform cost creates a barrier to education for the very poor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Simmons-Zuilkowski [ 105 ] found that in South Africa enrollment rates among the very poor are lower because of cost of uniforms. In Kenya, Mutengi [ 106 ] found a statistically significant link between uniform cost and education access, and Green et al [ 107 ], Sitieni and Pillay [ 108 ] and Cho et al [ 109 ] describe free uniform as part of support and incentive packages for at-risk children to attend school [ 110 ]. In Ghana, Alagbela [ 111 ] and Akaguri [ 112 ] show that uniform cost creates a barrier to education for the very poor.…”
Section: Resultsmentioning
confidence: 99%
“…Paradoxically, uniforms can worsen inequity. Worldwide, for the very poorest students, the cost of a uniform may be prohibitive, creating a barrier to education before the students even arrive on school grounds [ 83 , 105 107 , 109 112 , 114 – 116 , 137 ]. For some students the disadvantages will be cumulative.…”
Section: Discussionmentioning
confidence: 99%
“…The two previous procedures are in essence, Linear Mixed-Effects Models. Recently, Anaya & Al-Delaimy 2017 [68] and Green et al 2019 [69] did implement multilevel modeling for longitudinal data using linear mixed-effects models with R software [70] using the lme4 package.…”
Section: Time-evolution Modelingmentioning
confidence: 99%
“…Additionally, the hierarchical linear model in [78] and the multilevel modeling of longitudinal data in [79] were fitted using SPSS (MIXED) and SAS (PROC MIXED) procedures respectively. On the other hand, Green et al 2019 [69] used linear mixed-effect models with R software [70] by means of lme4 package, to fit multilevel models with random intercepts for schools and random intercepts and random slopes for time at the individual level since students are nested within waves.…”
mentioning
confidence: 99%
“…Green, Cho, Gallis, and Puffer () shift gear from observation to experiment. They report data from a powerful randomised controlled trial (with longitudinal follow‐ups over 4 years) of the value of practical support for school attendance as a driver of mental health resilience in Kenyan adolescents.…”
mentioning
confidence: 99%